SOME PATHOGENETIC FEATURES A COMBINATION OF PEPTIC ULCER OF STOMACH AND DUODENUM, ASSOCIATED WITH ARTERIAL HYPERTENSION AND DIABETES MELLITUS TYPE 2 - Сіцінська, І.О. (World of Medicine and Biology, 2016)
The article is devoted to the study of functional state of endothelium in patients with peptic ulcer of stomach and duodenal ulcers in combination with arterial hypertension and diabetes mellitus type 2. We examined 80 patients (40 patients with peptic ulcer of stomach and duodenal ulcers, 40 patients with peptic ulcer of stomach and duodenal ulcers in combination with arterial hypertension and diabetes mellitus type 2). The disturbance of lipid metabolism and redox systems, which indicates a depletion of the reserves of antioxidant defenses, disorders of the vascular wall, accompanying the strengthening of destructive processes and increased severity of disease.